FABRICATION AND CHARACTERIZATION OF PECTIN/POLYVINYL ALCOHOL BIO-COMPOSITE FOR ENHANCED ANTIMICROBIAL ACTIVITY - N. Giruba; G.R. Bella (The Bioscan, 2025)
The blending of natural polysaccharide pectin with synthetic biodegradable polymer polyvinyl alcohol (PVA) aimed to develop a bio-composite with improved functional and structural properties. The bio-composite was fabricated through solution casting method, and its physicochemical characteristics were analysed using techniques such as FTIR, XRD, SEM and antimicrobial activity. FTIR analysis confirmed the successful interaction and hydrogen bonding between the functional groups of Pectin and PVA. XRD studies showed a reduction in crystallinity, indicating effective blending and partial amorphization of the bio-composite matrix. SEM analysis revealed the surface morphology of the prepared bio-composite and suggesting the strong interfacial compatibility between Pectin and PVA . Antimicrobial activity was assessed against common bacterial strains, and the bio-composite exhibited significant inhibitory effects, especially due to the bioactive nature of pectin and its synergistic interaction with PVA. These findings demonstrate that Pectin/PVA bio-composite hold promising potential for applications in antimicrobial packaging and biomedical materials.